2015
DOI: 10.1101/gad.267989.115
|View full text |Cite
|
Sign up to set email alerts
|

FoxP1 orchestration of ASD-relevant signaling pathways in the striatum

Abstract: Mutations in the transcription factor Forkhead box p1 (FOXP1) are causative for neurodevelopmental disorders such as autism. However, the function of FOXP1 within the brain remains largely uncharacterized. Here, we identify the gene expression program regulated by FoxP1 in both human neural cells and patient-relevant heterozygous Foxp1 mouse brains. We demonstrate a role for FoxP1 in the transcriptional regulation of autism-related pathways as well as genes involved in neuronal activity. We show that Foxp1 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
162
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(178 citation statements)
references
References 84 publications
15
162
1
Order By: Relevance
“…This targeting information, combined with the neural expression of miR-873-5p and its host gene LINGO2, strongly suggest a potential regulatory role in synapse development and function. We also found that the miR-873-5p variant binds to the transcription factor FOXP1 transcript, suggesting a dysregulation of FOXP1 expression, which has previously been shown to play a critical regulatory role in CNTNAP2 expression [83], as well as a functional role of striatal pathways important for vocal communication [84]. Despite this miRNA mutation being inherited from an unaffected parent, the measurable loss-of-binding in several ASD-risk genes leads us to postulate that it may contribute additively to ASD risk, particularly when combined with the mutation load from the mother with recorded BAP.…”
Section: Discussionmentioning
confidence: 51%
“…This targeting information, combined with the neural expression of miR-873-5p and its host gene LINGO2, strongly suggest a potential regulatory role in synapse development and function. We also found that the miR-873-5p variant binds to the transcription factor FOXP1 transcript, suggesting a dysregulation of FOXP1 expression, which has previously been shown to play a critical regulatory role in CNTNAP2 expression [83], as well as a functional role of striatal pathways important for vocal communication [84]. Despite this miRNA mutation being inherited from an unaffected parent, the measurable loss-of-binding in several ASD-risk genes leads us to postulate that it may contribute additively to ASD risk, particularly when combined with the mutation load from the mother with recorded BAP.…”
Section: Discussionmentioning
confidence: 51%
“…Measuring USVs is widely carried out in genetic ASD model mice (63), with phenotypes observed in models of Foxp1 (64), Cntnap2 (52), Tsc1 (20), Tsc2 (65), Nlgn3 (66), Nlgn4 (67), Shank1 (68), Shank2 (69), Shank3 (70) and Mecp2 (71). In support of our behavioral results, two recent studies have demonstrated that sumoylation in hippocampus can modify mammalian cognitive behaviors by altering hippocampal-dependent learning and memory by Ubc9, a E2 conjugating enzyme (72), and spatial memory by sumoylation of CREB (73).…”
Section: Discussionmentioning
confidence: 99%
“…De novo loss‐of‐function variants in the fork head box P1 ( FOXP1 ) gene have been identified in independent studies of individuals with ASD . Mice with constitutive heterozygous deletion of Foxp1 had reduced ultrasonic vocalizations . Brain‐specific homozygous Foxp1 knockout mice had morphological defects of the developing brain, several behavioral abnormalities, altered neuronal dendritic morphology, and reduced excitability of CA1 hippocampal pyramidal neurons.…”
Section: Transcription Factorsmentioning
confidence: 99%